Repercursiones perinatales tras violencia de género en la mujer embarazada. Una revisión bibliográfica actualizada - Marta De- (Universitat de Barcelona, 2019)
Pregnancy is not a protective factor against gender violence. On the contrary, it is a critical stage in which the vulnerability of women grows, contributing to the appearance, continuation and even the increase of violence. The aim of this study is to review of the scientific evidence of recent years about the relationship between gender violence in pregnant women and its effects on obstetric and perinatal outcomes. Method: A bibliographic review was made in Pubmed, Tripdatabase and Cochrane online databases, covering the last five years. The keywords used in the search were: intimate partner violence, domestic violence, pregnancy, premature, low birth weight, birth outcomes. Results: Scientific evidence has studied the effects of gender violence on four variables: premature birth (PP), low birth weight (LBW), intrauterine growth restriction (IUGR), and small for the gestational age (SGA). Conclusions: Due to the consequences on maternal and fetal health caused by gender-based violence, the studies defend the need to establish routine examinations in each trimester of pregnancy by health workers who are in contact with pregnant women. In this way, it will be more likely to detect a possible risk situation and thus avoid harm and the death of women and their babies.